Modes of inhibition used by phage anti-CRISPRs to evade type I-C Cascade - O’Brien, Roisin E.; Bravo, Jack Peter Kelly; Ramos, Delisa; Hibshman, Grace N.; Wright, Jacquelyn T.; Taylor, David W. (bioRxiv)
Cascades are RNA-guided multi-subunit CRISPR-Cas surveillances complexes that target foreign nucleic acids for destruction. Here, we present a 2.9-Å resolution cryo-electron (cryo-EM) structure of the D. vulgaris type I-C Cascade bound to a double-stranded (ds)DNA target. Our data shows how the 5’-TTC-3’ protospacer adjacent motif (PAM) sequence is recognized, and provides a unique mechanism through which the displaced, single-stranded non-target strand (NTS) is stabilized via stacking interactions with protein subunits in order to favor R-loop formation and prevent dsDNA re-annealing. Additionally, we provide structural insights into how diverse anti-CRISPR (Acr) proteins utilize distinct strategies to achieve a shared mechanism of type I-C Cascade inhibition by blocking initial DNA binding. These observations provide a structural basis for directional R-loop formation and reveal how divergent Acr proteins have converged upon common molecular mechanisms to efficiently shut down CRISPR immunity.

Assembly of multi-subunit fusion proteins into the RNA-targeting type III-D CRISPR-Cas effector complex - Schwartz, Evan A.; Bravo, Jack Peter Kelly; Macias, Luis A.; McCafferty, Caitlyn L.; Dangerfield, Tyler L.; Walker, Jada N.; Brodbelt, Jennifer S.; Fineran, Peter C.; Fagerlund, Robert D.; Taylor, David W. (bioRxiv)
CRISPR (Clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) systems are a type of adaptive immune response in bacteria and archaea that utilize crRNA (CRISPR RNA)-guided effector complexes to target complementary RNA or DNA for destruction. The prototypical type III-A and III-B CRISPR-Cas systems utilize multi-subunit effector complexes composed of individual proteins to cleave ssRNA targets at 6-nt intervals, as well as non-specifically degrading ssDNA and activating cyclic oligoadenylate (cOA) synthesis. Recent studies have shown that type III systems can contain subunit fusions yet maintain canonical type III RNA-targeting capabilities. To understand how a multi-subunit fusion effector functions, we determine structures of a variant type III-D effector and biochemically characterize how it cleaves RNA targets. These findings provide insights into how multi-subunit fusion proteins are tethered together and assemble into an active and programmable RNA endonuclease, how the effector utilizes a novel mechanism for target RNA seeding, and the structural basis for the evolution of type III effector complexes. Furthermore, our results provide a blueprint for fusing subunits in class 1 effectors for design of user-defined effector complexes with disparate activities. Important note While this manuscript was in preparation, a manuscript describing the structure of the type III-E effector was published 1 . We reference these important findings; however, a careful comparison of the structures will follow once the coordinates have been released by the PDB.

Large-scale structural rearrangements unleash indiscriminate nuclease activity of CRISPR-Cas12a2 - Bravo, Jack Peter Kelly; Hallmark, Thom; Naegle, Bronson; Beisel, Chase L.; Jackson, Ryan N.; Taylor, David W. (bioRxiv)
Cas12a2 is a CRISPR-associated nuclease that performs RNA-guided degradation of non-specific single-stranded (ss)RNA, ssDNA and double-stranded (ds)DNA upon recognition of a complementary RNA target, culminating in abortive infection (Dmytrenko 2022). Here, we report structures of Cas12a2 in binary, ternary, and quaternary complexes to reveal a complete activation pathway. Our structures reveal that Cas12a2 is autoinhibited until binding a cognate RNA target, which exposes the RuvC active site within a large, positively charged cleft. Double-stranded DNA substrates are captured through duplex distortion and local melting, stabilized by pairs of ‘aromatic clamp’ residues that are crucial for dsDNA degradation and in vivo immune system function. Our work provides a structural basis for this unprecedented mechanism of abortive infection to achieve population-level immunity, which can be leveraged to create rational mutants that degrade a spectrum of collateral substrates.

Spectrum of equivariant cohomology as a fixed point scheme - Hausel, Tamás; Rychlewicz, Kamil P (arXiv)
An action of a complex reductive group G on a smooth projective variety X is regular when all regular unipotent elements in G act with finitely many fixed points. Then the complex G-equivariant cohomology ring of X is isomorphic to the coordinate ring of a certain regular fixed point scheme. Examples include partial flag varieties, smooth Schubert varieties and Bott-Samelson varieties. We also show that a more general version of the fixed point scheme allows a generalisation to GKM spaces, such as toric varieties.

Umbrella meshes: Elastic mechanisms for freeform shape deployment - Ren, Yingying; Kusupati, Uday; Panetta, Julian; Isvoranu, Florin; Pellis, Davide; Chen, Tian; Pauly, Mark (ACM Transactions on Graphics)
We present a computational inverse design framework for a new class of volumetric deployable structures that have compact rest states and deploy into bending-active 3D target surfaces. Umbrella meshes consist of elastic beams, rigid plates, and hinge joints that can be directly printed or assembled in a zero-energy fabrication state. During deployment, as the elastic beams of varying heights rotate from vertical to horizontal configurations, the entire structure transforms from a compact block into a target curved surface. Umbrella Meshes encode both intrinsic and extrinsic curvature of the target surface and in principle are free from the area expansion ratio bounds of past auxetic material systems. We build a reduced physics-based simulation framework to accurately and efficiently model the complex interaction between the elastically deforming components. To determine the mesh topology and optimal shape parameters for approximating a given target surface, we propose an inverse design optimization algorithm initialized with conformal flattening. Our algorithm minimizes the structure's strain energy in its deployed state and optimizes actuation forces so that the final deployed structure is in stable equilibrium close to the desired surface with few or no external constraints. We validate our approach by fabricating a series of physical models at various scales using different manufacturing techniques.

BFF: Foundational and automated verification of bitfield-manipulating programs - Zhu, Fengmin; Sammler, Michael Joachim; Lepigre, Rodolphe; Dreyer, Derek; Garg, Deepak (Proceedings of the ACM on Programming Languages)
Low-level systems code often needs to interact with data, such as page table entries or network packet headers, in which multiple pieces of information are packaged together as bitfield components of a single machine integer and accessed via bitfield manipulations (e.g., shifts and masking). Most existing approaches to verifying such code employ SMT solvers, instantiated with theories for bit vector reasoning: these provide a powerful hammer, but also significantly increase the trusted computing base of the verification toolchain. In this work, we propose an alternative approach to the verification of bitfield-manipulating systems code, which we call BFF. Building on the RefinedC framework, BFF is not only highly automated (as SMT-based approaches are) but also foundational---i.e., it produces a machine-checked proof of program correctness against a formal semantics for C programs, fully mechanized in Coq. Unlike SMT-based approaches, we do not try to solve the general problem of arbitrary bit vector reasoning, but rather observe that real systems code typically accesses bitfields using simple, well-understood programming patterns: the layout of a bit vector is known up front, and its bitfields are accessed in predictable ways through a handful of bitwise operations involving bit masks. Correspondingly, we center our approach around the concept of a structured bit vector---i.e., a bit vector with a known bitfield layout---which we use to drive simple and predictable automation. We validate the BFF approach by verifying a range of bitfield-manipulating C functions drawn from real systems code, including page table manipulation code from the Linux kernel and the pKVM hypervisor.

Islaris: Verification of machine code against authoritative ISA semantics - Sammler, Michael Joachim; Hammond, Angus; Lepigre, Rodolphe; Campbell, Brian; Pichon-Pharabod, Jean; Dreyer, Derek; Garg, Deepak; Sewell, Peter (Proceedings of the 43rd ACM SIGPLAN International Conference on Programming Language Design and Implementation)
Recent years have seen great advances towards verifying large-scale systems code. However, these verifications are usually based on hand-written assembly or machine-code semantics for the underlying architecture that only cover a small part of the instruction set architecture (ISA). In contrast, other recent work has used Sail to establish formal models for large real-world architectures, including Armv8-A and RISC-V, that are comprehensive (complete enough to boot an operating system or hypervisor) and authoritative (automatically derived from the Arm internal model and validated against the Arm validation suite, and adopted as the official formal specification by RISC-V International, respectively). But the scale and complexity of these models makes them challenging to use as a basis for verification. In this paper, we propose Islaris, the first system to support verification of machine code above these complete and authoritative real-world ISA specifications. Islaris uses a novel combination of SMT-solver-based symbolic execution (the Isla symbolic executor) and automated reasoning in a foundational program logic (a new separation logic we derive using Iris in Coq). We show that this approach can handle Armv8-A and RISC-V machine code exercising a wide range of systems features, including installing and calling exception vectors, code parametric on a relocation address offset (from the production pKVM hypervisor); unaligned access faults; memory-mapped IO; and compiled C code using inline assembly and function pointers.

VIP: Verifying real-world C idioms with integer-pointer casts - Lepigre, Rodolphe; Sammler, Michael Joachim; Memarian, Kayvan; Krebbers, Robbert; Dreyer, Derek; Sewell, Peter (Proceedings of the ACM on Programming Languages)
Systems code often requires fine-grained control over memory layout and pointers, expressed using low-level (e.g., bitwise) operations on pointer values. Since these operations go beyond what basic pointer arithmetic in C allows, they are performed with the help of integer-pointer casts. Prior work has explored increasingly realistic memory object models for C that account for the desired semantics of integer-pointer casts while also being sound w.r.t. compiler optimisations, culminating in PNVI, the preferred memory object model in ongoing discussions within the ISO WG14 C standards committee. However, its complexity makes it an unappealing target for verification, and no tools currently exist to verify C programs under PNVI. In this paper, we introduce VIP, a new memory object model aimed at supporting C verification. VIP sidesteps the complexities of PNVI with a simple but effective idea: a new construct that lets programmers express the intended provenances of integer-pointer casts explicitly. At the same time, we prove VIP compatible with PNVI, thus enabling verification on top of VIP to benefit from PNVI’s validation with respect to practice. In particular, we build a verification tool, RefinedC-VIP, for verifying programs under VIP semantics. As the name suggests, RefinedC-VIP extends the recently developed RefinedC tool, which is automated yet also produces foundational proofs in Coq. We evaluate RefinedC-VIP on a range of systems-code idioms, and validate VIP’s expressiveness via an implementation in the Cerberus C semantics.

Simuliris: A separation logic framework for verifying concurrent program optimizations - Gäher, Lennard; Sammler, Michael Joachim; Spies, Simon; Jung, Ralf; Dang, Hoang-Hai; Krebbers, Robbert; Kang, Jeehoon; Dreyer, Derek (Proceedings of the ACM on Programming Languages)
Today’s compilers employ a variety of non-trivial optimizations to achieve good performance. One key trick compilers use to justify transformations of concurrent programs is to assume that the source program has no data races: if it does, they cause the program to have undefined behavior (UB) and give the compiler free rein. However, verifying correctness of optimizations that exploit this assumption is a non-trivial problem. In particular, prior work either has not proven that such optimizations preserve program termination (particularly non-obvious when considering optimizations that move instructions out of loop bodies), or has treated all synchronization operations as external functions (losing the ability to reorder instructions around them). In this work we present Simuliris, the first simulation technique to establish termination preservation (under a fair scheduler) for a range of concurrent program transformations that exploit UB in the source language. Simuliris is based on the idea of using ownership to reason modularly about the assumptions the compiler makes about programs with well-defined behavior. This brings the benefits of concurrent separation logics to the space of verifying program transformations: we can combine powerful reasoning techniques such as framing and coinduction to perform thread-local proofs of non-trivial concurrent program optimizations. Simuliris is built on a (non-step-indexed) variant of the Coq-based Iris framework, and is thus not tied to a particular language. In addition to demonstrating the effectiveness of Simuliris on standard compiler optimizations involving data race UB, we also instantiate it with Jung et al.’s Stacked Borrows semantics for Rust and generalize their proofs of interesting type-based aliasing optimizations to account for concurrency.

Self-lensing flares from black hole binaries: General-relativistic ray tracing of black hole binaries - Davelaar, Jordy; Haiman, Zoltán (Physical Review D)
The self-lensing of a massive black hole binary (MBHB), which occurs when the two BHs are aligned close to the line of sight, is expected to produce periodic, short-duration flares. Here we study the shapes of self-lensing flares (SLFs) via general-relativistic ray tracing in a superimposed binary BH metric, in which the emission is generated by geometrically thin accretion flows around each component. The suite of models covers eccentric binary orbits, black hole spins, unequal mass binaries, and different emission model geometries. We explore the above parameter space and report how the light curves change as a function of, e.g., binary separation, inclination, and eccentricity. We also compare our light curves to those in the microlensing approximation, and show how strong deflections, as well as time-delay effects, change the size and shape of the SLF. If gravitational waves (GWs) from the inspiraling MBHB are observed by LISA, SLFs can help securely identify the source and localizing it on the sky, and to constrain the graviton mass by comparing the phasing of the SLFs and the GWs. Additionally, when these systems are viewed edge-on the SLF shows a distinct dip that can be directly correlated with the BH shadow size. This opens a new way to measure BH shadow sizes in systems that are unresolvable by current VLBI facilities.

AGN as potential factories for eccentric black hole mergers - Samsing, J.; Bartos, I.; D’Orazio, D. J.; Haiman, Zoltán; Kocsis, B.; Leigh, N. W. C.; Liu, B.; Pessah, M. E.; Tagawa, H. (Nature)
There is some weak evidence that the black hole merger named GW190521 had a non-zero eccentricity. In addition, the component black holes' masses exceeded the limit predicted by stellar evolution. The large masses can be explained by successive mergers, which may be efficient in gas disks surrounding active galactic nuclei (AGN), but it is difficult to maintain an eccentric orbit all the way to the merger, as basic physics would argue for circularization. Here we show that AGN-disk environments can lead to an excess of eccentric mergers, if the interactions between single and binary black holes are frequent, and occur with mutual inclinations of less than a few degrees. We further illustrate that this eccentric population has a different distribution of the inclination between the spin vectors of the black holes and their orbital angular momentum at merger, referred to as the spin-orbit tilt, compared to the remaining circular mergers.

Self-Lensing flares from black hole binaries: Observing black hole shadows via light curve tomography - Davelaar, Jordy; Haiman, Zoltán (Physical Review Letters)
Supermassive black hole (BH) binaries are thought to produce self-lensing flares (SLFs) when the two BHs are aligned with the line of sight. If the binary orbit is observed nearly edge-on, we find a distinct feature in the light curve imprinted by the relativistic shadow around the background (“source”) BH. We study this feature by ray tracing in a binary model and predict that 1% of the current binary candidates could show this feature. Our BH tomography method proposed here could make it possible to extract BH shadows that are spatially unresolvable by high-resolution very long base line interferometry (VLBI).

How binaries accrete: Hydrodynamic simulations with passive tracer particles - Tiede, Christopher; Zrake, Jonathan; MacFadyen, Andrew; Haiman, Zoltán (The Astrophysical Journal)
Linear analysis of gas flows around orbiting binaries suggests that a centrifugal barrier ought to clear a low-density cavity around the binary and inhibit mass transfer onto it. Modern hydrodynamics simulations have confirmed the low-density cavity, but show that any mass flowing from large scales into the circumbinary disk is eventually transferred onto the binary components. Even though many numerical studies confirm this picture, it is still not understood precisely how gas parcels overcome the centrifugal barrier and ultimately accrete. We present a detailed analysis of the binary accretion process, using an accurate prescription for evolving grid-based hydrodynamics with Lagrangian tracer particles that track the trajectories of individual gas parcels. We find that binary accretion can be described in four phases: (1) gas is viscously transported through the circumbinary disk up to the centrifugal barrier at the cavity wall, (2) the cavity wall is tidally distorted into accretion streams consisting of near-ballistic gas parcels on eccentric orbits, (3) the portion of each stream moving inwards of an ``accretion horizon'' radius r¯≃a -- the radius beyond which no material is returned to the cavity wall -- becomes bound to a minidisk orbiting an individual binary component, and (4) the minidisk gas accretes onto the binary component through the combined effect of viscous and tidal stresses.

Supercritical growth pathway to overmassive black holes at cosmic dawn: Coevolution with massive quasar hosts - Hu, Haojie; Inayoshi, Kohei; Haiman, Zoltán; Li, Wenxiu; Quataert, Eliot; Kuiper, Rolf (The Astrophysical Journal)
Observations of the most luminous quasars at high redshifts (z>6) have revealed that the largest supermassive black holes (SMBHs) at those epochs tend to be substantially overmassive relative to their host galaxies compared to the local relations, suggesting they experienced rapid early growth phases. We propose an assembly model for the SMBHs that end up in rare massive ∼1012 M⊙ host halos at z∼6−7, applying a kinetic feedback prescription for BHs accreting above the Eddington rate, provided by radiation hydrodynamic simulations for the long-term evolution of the accretion-flow structure. The large inflow rates into these halos during their assembly enable the formation of >109 M⊙ SMBHs by z∼6, even starting from stellar-mass seeds at z∼30, and even in the presence of outflows that reduce the BH feeding rate, especially at early times. This mechanism also naturally yields a high BH-to-galaxy mass ratio of >0.01 before the SMBH mass reaches MBH>109 M⊙ by z∼6. These fast-growing SMBH progenitors are bright enough to be detected by upcoming observations with the James Webb Space Telescope over a wide range of redshift (7<z<15), regardless of how they were seeded.

Tidal disruption on stellar-mass black holes in active galactic nuclei - Yang, Y.; Bartos, I.; Fragione, G.; Haiman, Zoltán; Kowalski, M.; Márka, S.; Perna, R.; Tagawa, H. (The Astrophysical Journal Letters)
Active galactic nuclei (AGNs) can funnel stars and stellar remnants from the vicinity of the galactic center into the inner plane of the AGN disk. Stars reaching this inner region can be tidally disrupted by the stellar-mass black holes in the disk. Such micro tidal disruption events (micro-TDEs) could be a useful probe of stellar interaction with the AGN disk. We find that micro-TDEs in AGNs occur at a rate of ∼170 Gpc−3 yr−1. Their cleanest observational probe may be the electromagnetic detection of tidal disruption in AGNs by heavy supermassive black holes (M• ≳ 108 M⊙) that cannot tidally disrupt solar-type stars. The reconstructed rate of such events from observations, nonetheless, appears to be much lower than our estimated micro-TDE rate. We discuss two such micro-TDE candidates observed to date (ASASSN-15lh and ZTF19aailpwl).

Simultaneously constraining cosmology and baryonic physics via deep learning from weak lensing - Lu, Tianhuan; Haiman, Zoltán; Zorrilla Matilla, José Manuel (Monthly Notices of the Royal Astronomical Society)
Ongoing and planned weak lensing (WL) surveys are becoming deep enough to contain information on angular scales down to a few arcmin. To fully extract information from these small scales, we must capture non-Gaussian features in the cosmological WL signal while accurately accounting for baryonic effects. In this work, we account for baryonic physics via a baryonic correction model that modifies the matter distribution in dark matter-only N-body simulations, mimicking the effects of galaxy formation and feedback. We implement this model in a large suite of ray-tracing simulations, spanning a grid of cosmological models in Ωm−σ8 space. We then develop a convolutional neural network (CNN) architecture to learn and constrain cosmological and baryonic parameters simultaneously from the simulated WL convergence maps. We find that in a Hyper-Suprime Cam-like survey, our CNN achieves a 1.7× tighter constraint in Ωm−σ8 space (1σ area) than the power spectrum and 2.1× tighter than the peak counts, showing that the CNN can efficiently extract non-Gaussian cosmological information even while marginalizing over baryonic effects. When we combine our CNN with the power spectrum, the baryonic effects degrade the constraint in Ωm−σ8 space by a factor of 2.4, compared to the much worse degradation by a factor of 4.7 or 3.7 from either method alone.

Cosmological constraints from weak lensing peaks: Can halo models accurately predict peak counts? - Sabyr, Alina; Haiman, Zoltán; Matilla, José Manuel Zorrilla; Lu, Tianhuan (Physical Review D)
In order to extract full cosmological information from next-generation large and high-precision weak lensing (WL) surveys (e.g., Euclid, Roman, and LSST), higher-order statistics that probe the small-scale, nonlinear regime of large-scale structure (LSS) need to be utilized. WL peak counts, which trace overdensities in the cosmic web, are one promising and simple statistic for constraining cosmological parameters. The physical origin of WL peaks have previously been linked to dark matter halos along the line of sight, and this peak-halo connection has been used to develop various semianalytic halo-based models for predicting peak counts. Here, we study the origin of WL peaks and the effectiveness of halo-based models for WL peak counts using a suite of ray-tracing N-body simulations. We compare WL peaks in convergence maps from the full simulations to those in maps created from only particles associated with halos—the latter playing the role of a “perfect” halo model. We find that, while halo-only contributions are able to replicate peak counts qualitatively well, halos do not explain all WL peaks. Halos particularly underpredict negative peaks, which are associated with local overdensities in large-scale underdense regions along the line of sight. In addition, neglecting nonhalo contributions to peaks counts leads to a significant bias on the parameters (Ωm, 𝜎8) for surveys larger than ⪆100  deg2. We conclude that other elements of the cosmic web, outside and far away from dark matter halos, need to be incorporated into models of WL peaks in order to infer unbiased cosmological constraints.

Can stellar-mass black hole growth disrupt disks of active galactic nuclei? The role of mechanical feedback - Tagawa, Hiromichi; Kimura, Shigeo S.; Haiman, Zoltán; Perna, Rosalba; Tanaka, Hidekazu; Bartos, Imre (The Astrophysical Journal)
Stellar-mass BHs (sBHs) are predicted to be embedded in active galactic nuclei (AGN) disks due to gravitational drag and in-situ star formation. However, we find that due to a high gas density in an AGN disk environment, compact objects may rapidly grow to intermediate-mass BHs and deplete matter from the AGN disk unless accretion is suppressed by some feedback process(es). These consequences are inconsistent with AGN observations and the dynamics of the Galactic center. Here we consider mechanical feedback mechanisms for the reduction of gas accretion. Rapidly accreting sBHs launch winds and/or jets via the Blandford-Znajek mechanism, which produce high-pressure shocks and cocoons. Such a shock and cocoon can spread laterally in the plane of the disk, eject the outer regions of a circum-sBH disk (CsBD) and puncture a hole in the AGN disk with horizontal size comparable to the disk scale-height. Since the depletion timescale of the bound CsBD is much shorter than the resupply timescale of gas to the sBH, the time-averaged accretion rate onto sBHs is reduced by this process by a factor of ∼10--100. This feedback mechanism can therefore help alleviate the sBH over-growth and AGN-disk depletion problems. On the other hand, we find that cocoons of jets can unbind a large fraction of the gas accreting in the disks of less massive SMBHs, which may help explain the dearth of high-Eddington ratio AGNs with SMBH mass ≲105M⊙.

How long do high redshift massive black hole seeds remain outliers in black hole versus host galaxy relations? - Scoggins, Matthew T; Haiman, Zoltán; Wise, John H (Monthly Notices of the Royal Astronomical Society)
The existence of 109 M⊙ supermassive black holes (SMBHs) within the first billion years of the Universe remains a puzzle in our conventional understanding of black hole formation and growth. Several suggested formation pathways for these SMBHs lead to a heavy seed, with an initial black hole mass of 104–106 M⊙. This can lead to an overly massive BH galaxy (OMBG), whose nuclear black hole’s mass is comparable to or even greater than the surrounding stellar mass: the black hole to stellar mass ratio is Mbh/M* ≫ 10−3, well in excess of the typical values at lower redshift. We investigate how long these newborn BHs remain outliers in the Mbh − M* relation, by exploring the subsequent evolution of two OMBGs previously identified in the Renaissance simulations. We find that both OMBGs have Mbh/M* > 1 during their entire life, from their birth at z ≈ 15 until they merge with much more massive haloes at z ≈ 8. We find that the OMBGs are spatially resolvable from their more massive, 1011 M⊙, neighbouring haloes until their mergers are complete at z ≈ 8. This affords a window for future observations with JWST and sensitive X-ray telescopes to diagnose the heavy-seed scenario, by detecting similar OMBGs and establishing their uniquely high black hole-to-stellar mass ratio.

Multimessenger constraints on magnetic fields in merging black hole–neutron star binaries - D’Orazio, Daniel J.; Haiman, Zoltán; Levin, Janna; Samsing, Johan; Vigna-Gómez, Alejandro (The Astrophysical Journal)
The LIGO–Virgo–KAGRA Collaboration recently detected gravitational waves (GWs) from the merger of black hole–neutron star (BHNS) binary systems GW200105 and GW200115. No coincident electromagnetic (EM) counterparts were detected. While the mass ratio and BH spin in both systems were not sufficient to tidally disrupt the NS outside the BH event horizon, other, magnetospheric mechanisms for EM emission exist in this regime and depend sensitively on the NS magnetic field strength. Combining GW measurements with EM flux upper limits, we place upper limits on the NS surface magnetic field strength above which magnetospheric emission models would have generated an observable EM counterpart. We consider fireball models powered by the black hole battery mechanism, where energy is output in gamma rays over ≲1 s. Consistency with no detection by Fermi-GBM or INTEGRAL SPI-ACS constrains the NS surface magnetic field to ≲1015 G. Hence, joint GW detection and EM upper limits rule out the theoretical possibility that the NSs in GW200105 and GW200115, and the putative NS in GW190814, retain dipolar magnetic fields ≳1015 G until merger. They also rule out formation scenarios where strongly magnetized magnetars quickly merge with BHs. We alternatively rule out operation of the BH-battery-powered fireball mechanism in these systems. This is the first multimessenger constraint on NS magnetic fields in BHNS systems and a novel approach to probe fields at this point in NS evolution. This demonstrates the constraining power that multimessenger analyses of BHNS mergers have on BHNS formation scenarios, NS magnetic field evolution, and the physics of BHNS magnetospheric interactions.